A case of blindness associated with myocardial infarction. Issue 656 (June 1980) - Brettle, R. P.
Abstract : A patient presented to hospital with sudden onset of blindness which was subsequently shown both clinically and by radionucleotide scanning to be cortical in nature. Four days before admission he had suffered 2 short episodes of aching jaw, dizziness, and profuse sweating. Myocardial infarction was confirmed by serial ECGs and cardiac enzymes. His cortical blindness was thought to be secondary to an embolus from a myocardial mural thrombus. A review of the literature revealed 5 previous patients with cortical blindness and associated myocardial infarction. In 2 of these, blindness followed within days of the myocardial infarct, but in none was it the presenting feature of a myocardial infarct.